Deep sequencing shows low‐level oncogenic hepatitis B virus variants persists post–liver transplant despite potent anti‐HBV prophylaxis. Issue 6 (6th February 2018) - Lau, K. C. K.; Osiowy, C.; Giles, E.; Lusina, B.; van Marle, G.; Burak, K. W.; Coffin, C. S.
Summary: Recent studies suggest that withdrawal of hepatitis B immune globulin (HBIG) and nucleos(t)ide analogues (NA) prophylaxis may be considered in HBV surface antigen (HBsAg)‐negative liver transplant (LT) recipients with a low risk of disease recurrence. However, the frequency of occult HBV infection (OBI) and HBV variants after LT in the current era of potent NA therapy is unknown. Twelve LT recipients on prophylaxis were tested in matched plasma and peripheral blood mononuclear cells (PBMCs) for HBV quasispecies by in‐house nested PCR and next‐generation sequencing of amplicons. HBV covalently closed circular DNA (cccDNA) was detected in Hirt DNA isolated from PBMCs with cccDNA‐specific primers and confirmed by nucleic acid hybridization and Sanger sequencing. HBV mRNA in PBMC was detected with reverse‐transcriptase nested PCR. In LT recipients on immunosuppressive therapy (10/12 male; median age 57.5 [IQR: 39.8‐66.5]; median follow‐up post‐LT 60 months; 6 pre‐LT hepatocellular carcinoma [HCC]), 9 were HBsAg‐. HBV DNA was detected in all plasma and PBMC tested; cccDNA and/or mRNA was detected in the PBMC of 10/12 patients. Significant HBV quasispecies diversity (ie 143‐2212 nonredundant HBV species) was noted in both sites, and single nucleotide polymorphisms associated with cirrhosis and HCC were detected at varying frequencies. In conclusion, OBI and HBV variants associated with severe liver disease persist in LT recipients on prophylaxis. Although HBV control and cccDNA transcriptional silencing may occur despite immunosuppression, complete virological eradication does not occur in LT recipients with a history of HBV‐related end‐stage liver disease.